Neoplasms of the head and neck in Iranian children and adolescents - Saede Atarbashi-Moghadam; Mohammad Taghi Haghi Ashtiani; Maryam Barati; Soran Sijanivandi (Indian Journal of Medical and Paediatric Oncology)
Introduction: Head and neck neoplasms afflict all age groups including children. They manifest with various histological features and clinical behaviors. This study's aim was to provide data and analysis of the prevalence of head and neck neoplasms among the Iranian children and adolescents to help pathologists and clinicians make informed diagnosis and treatment decisions. Materials and Methods: This retrospective study was based on medical records of children and adolescents (≤18 years) documented at a prestigious children's medical center stationed in Tehran, Iran. Cases diagnosed with head and neck tumors recorded from 2005 to 2016 were selected. Patients' age and sex, tumors' sites, and microscopic types were assessed. Data analysis was performed using descriptive statistics. Results: Of the 41,409 available pediatric patients' records documented over 12 years, 418 cases (1.01%) recorded head and neck tumors. Of these 418 cases, 15 recorded metastatic tumors (3.58%) and 403 recorded primary tumors. Of the primary tumors, 386 were found in the soft tissue (95.78%) and 17 in the bone (4.22%). The primary tumor patients' mean age was 5.46 years, including boys (59.8%) and girls (40.2%). The neck was the most common primary tumors' location (57.32%). Of all the primary tumors, 54.6% were benign neoplasms and 45.4% malignant. The commonest benign tumors were hemangioma/lymphangioma, and the most common malignancy was lymphoma. Mesenchymal neoplasms were the most common microscopic group followed by hematopoietic tumors. Conclusions: The analysis of these data indicates that the prevalence of pediatric head and neck tumors in the Iranian population is similar to other countries.